Impersonator. - Zweig, Janet (Chain, 2004)
Presents the author's accounts of a text-generating program for a commission for a public artwork at a technology center in Santa Fe, New Mexico. Artistic possibility of computer programming; Function of the mechanical flip signs that announce trains in Europe; Connection of all units to a computer within the sign that receives codes.